The deficit of current account balances and budgetary deficit in countries in transition - Sandra Krtalic; Ines Kersan (European Regional Science Association (ERSA), 1998)
In restructuring process of their own economies, countries in transition deal with many common problems. One of the problems that transition brought to those countries is deficit in current account, as well as budget deficit. Deficits represent limit to a healthy and fast economic development and progress. Balance in balance of payments, as well as balanced budget are components of macroeconomic system. The authors will give an review of activities on deficits in countries in transition, and try to create interdependence of activities of those two deficits.
Keywords: 330